Baby dinosaurs on the ark?: the Bible and modern science and the trouble of making it all fit - Ray, Janet Kellogg (Wm. B. Eerdmans Publishing Co, 2021)
"An exploration of creationism and the science of origins that shows how a literal reading of the Bible-particularly the book of Genesis-can lead to distortions of scientific reality"--